Risk Factors for Intravesical Recurrence after Minimally Invasive Nephroureterectomy for Upper Tract Urothelial Cancer (ROBUUST Collaboration). Issue 3 (21st September 2021) - Katims, Andrew B.; Say, Rollin; Derweesh, Ithaar; Uzzo, Robert; Minervini, Andrea; Wu, Zhenjie; Abdollah, Firas; Sundaram, Chandru; Ferro, Matteo; Rha, Koon; Mottrie, Alex; Rosiello, Giuseppe; et al.
Abstract : Purpose: Intravesical recurrence (IVR) after radical nephroureterectomy (RNU) for upper tract urothelial carcinoma (UTUC) has an incidence of approximately 20%–50%. Studies to date have been composed of mixed treatment cohorts—open, laparoscopic and robotic. The objective of this study is to assess clinicopathological risk factors for intravesical recurrence after RNU for UTUC in a completely minimally invasive cohort. Materials and Methods: We performed a multicenter, retrospective analysis of 485 patients with UTUC without prior or concurrent bladder cancer who underwent robotic or laparoscopic RNU. Patients were selected from an international cohort of 17 institutions across the United States, Europe and Asia. Univariate and multiple Cox regression models were used to identify risk factors for bladder recurrence. Results: A total of 485 (396 robotic, 89 laparoscopic) patients were included in analysis. Overall, 110 (22.7%) of patients developed IVR. The average time to recurrence was 15.2 months (SD 15.5 months). Hypertension was a significant risk factor on multiple regression (HR 1.99, CI 1.06; 3.71, p=0.030). Diagnostic ureteroscopic biopsy incurred a 50% higher chance of developing IVR (HR 1.49, CI 1.00; 2.20, p=0.048). Treatment specific risk factors included positive surgical margins (HR 3.36, CI 1.36; 8.33, p=0.009) and transurethral resection for bladder cuff management (HR 2.73, CI 1.10; 6.76, p=0.031). Conclusions: IVR after minimally invasive RNU for UTUC is a relatively common event. Risk factors include a ureteroscopic biopsy, transurethral resection of the bladder cuff, and positive surgical margins. When possible, avoidance of transurethral resection of the bladder cuff and alternative strategies for obtaining biopsy tissue sample should be considered.